(untitled) (REMUNOM, 2024)
Medicinal plants produce a large amount of bioactive molecules, among which fixed oils stand out, known for their high density and biological activities. This study evaluated: yield, chemical profile and allelopathic potential of fixed oil from the pulp of Caryocar villosum (Aubl.) Pers. on the development of lettuce and tomato seeds. The allelopathic test was carried out at the Federal University of Amazonas in Itacoatiara. The fixed oil of Caryocar villosum (Aubl.) Pers. The main compounds were: Propyl isovalerate (8.4%), Geraniol (9.3%), Terpinolene (9.7%), Safrole (13.7%) and Limonene (29.8%). The oil yield was 14.44% higher than the yields already described in the literature. All concentrations showed allelopathic activity, which allows us to evaluate that this species is a possible candidate for studies for the development of bioherbicides for allelopathy trials and industrial and agricultural application.